Blackhat - Mann, Michael, 1943-; Hemsworth, Chris; Wei, Tang, 1979-; Davis, Viola, 1965-; Gregson-Williams, Harry; Ross, Atticus, 1968-; Ross, Leopold (Composer) (Universal City, CA : Universal Studios Home Entertainment, 2015)
With the help of his American and Chinese partners, a furloughed convict hunts down a high-level cybercrime network.
Originally released as a motion picture in 2015.
Dolby digital 5.1, anamorphic wide screen 2.40:1.
Features: Creating reality.
Camera, Stuart Dryburgh ; production designer, Guy Hendrix Dyas ; editors, Mako Kamitsuna, Jeremiah O'Driscoll, Stephen E. Rivkin, Joe Walker ; music, Harry Gregson-Williams, Atticus Ross, Leo Ross.
Chris Hemsworth, Tang Wei, Viola Davis, Holt McCallany, Wang Leehorn.
MPAA rating: R.
Keywords: Prison furloughs -- Drama; Computer crimes -- Drama; Organized crime -- Drama; Crime films; Detective and mystery films; Action and adventure films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Thriller films; Feature films; Detective films; Mystery films